2007
DOI: 10.1186/1471-227x-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Cost-efficiency assessment of Advanced Life Support (ALS) courses based on the comparison of advanced simulators with conventional manikins

Abstract: BackgroundSimulation is an essential tool in modern medical education. The object of this study was to assess, in cost-effective measures, the introduction of new generation simulators in an adult life support (ALS) education program.MethodsTwo hundred fifty primary care physicians and nurses were admitted to ten ALS courses (25 students per course). Students were distributed at random in two groups (125 each). Group A candidates were trained and tested with standard ALS manikins and Group B ones with new gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
20
0
3
Order By: Relevance
“…Seven LOE 1 studies 140 -146 reported no effect on skills assessed using a manikin. Eleven LOE 1 studies tested the effect of simulation fidelity on the participants' knowledge using multiple-choice questions; nine of these studies found no effect 124,127,128,130,140,141,143,144,147 and two of the 11 studies demonstrated an improvement in participant knowledge with the more realistic techniques. 148,149 Two studies (LOE 3 136 ; LOE 4 138 ) that focused on resuscitation in trauma reported improved skill performance (on a manikin) with higher-fidelity simulation.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Seven LOE 1 studies 140 -146 reported no effect on skills assessed using a manikin. Eleven LOE 1 studies tested the effect of simulation fidelity on the participants' knowledge using multiple-choice questions; nine of these studies found no effect 124,127,128,130,140,141,143,144,147 and two of the 11 studies demonstrated an improvement in participant knowledge with the more realistic techniques. 148,149 Two studies (LOE 3 136 ; LOE 4 138 ) that focused on resuscitation in trauma reported improved skill performance (on a manikin) with higher-fidelity simulation.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…One LOE 1 study 144 questioned the cost-effectiveness of higher-fidelity approaches compared with standard manikins.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…144 Eight studies showed equal knowledge acquisition with realistic manikins when compared with lower-technology manikins. 128,130,138,[142][143][144][145][146] Three studies indicated that learner satisfaction was greater with realistic manikins. 130,138,142 There is insufficient evidence to recommend for or against the routine use of more realistic manikins to improve skills performance in actual resuscitations.…”
Section: Realistic Manikinsmentioning
confidence: 99%
“…138 -143 Use of more realistic manikins in training may incur substantially higher financial costs. 144 Eight studies showed equal knowledge acquisition with realistic manikins when compared with lower-technology manikins. 128,130,138,[142][143][144][145][146] Three studies indicated that learner satisfaction was greater with realistic manikins.…”
mentioning
confidence: 99%
“…"high" vs. "low fidelity simulation") macht den Vergleich unterschiedlicher Studien schwierig. Simulationstraining ging ziemlich konsistent [33,125,126,127,128,129,130,131,132,133,134,135,136], aber nicht generell [137,138,139,140,141,142,143] [187], die Durchführungsfertig-keiten [188], das Selbstvertrauen [189] und die Vertrautheit mit der Umgebung [190] der ALS-Helfer verbessern sowie Fehler im System und bei den Helfern identifizieren [191,192].…”
Section: Simulation Und Training Der Realistischen Wiederbelebungunclassified